Pengaruh Promosi Dan Mutasi Jabatan Terhadap Kinerja Pegawai Negeri Sipil Pada Sekretariat Daerah Kabupaten Dharmasraya - Sumiati; Eka Kemmala Arja (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The purpose of this study was to determine and analyze the effect of promotions and transfers on the performance of Civil Servants at the Regional Secretariat of Dharmasraya Regency. The method used in this thesis research is a quantitative method with an associative approach. The data collected in this study was obtained by distributing questionnaires using a Likert scale instrument with a sample of 68 civil servants, where the sampling method used was saturated sampling, which means the number of samples is the same as the total population. The data was processed using SPSS 16.00, with the results showing that the variables of promotion and mutation had a positive and significant effect on the performance of civil servants at the Regional Secretariat of Dharmasraya Regency. By knowing the relationship between these variables, promotion and transfer policies can be used to improve the performance of civil servants at the Regional Secretariat of Dharmasraya Regency.